Perbandingan Wedang Jahe Dan Sereh Lemon Dalam Mengurangi Keluhan Morning Sickness - Azizah, Imroatul; Amanda, Sifty Lia (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Pregnant women in their first trimester often experience morning sickness. If untreated, it can progress to hyperemesis gravidarum, leading to severe dehydration, organ damage, loss of consciousness, and even death. This study aims to compare the effectiveness of ginger tea and lemongrass lemon tea in reducing morning sickness complaints in first-trimester pregnant women. The study used a Pre-Experimental method with a One Group Pretest-Posttest Design and a quantitative approach. Data were collected using the PUQE-24 questionnaire from 63 respondents selected through purposive sampling. The teas were given twice daily (250 ml) for one week, and the results were analyzed using the Wilcoxon test. The findings showed a Sig. 2-Tailed value of 0.000 (p-value < 0.05), confirming the alternative hypothesis. Based on the mean value, lemongrass lemon tea was more effective than ginger tea. Both teas can serve as non-pharmacological interventions in complementary midwifery care to alleviate morning sickness. Government support is needed to ensure herbal ingredients are affordable for all. Keywords: Morning Sickness, Tea, Lemongrass Lemon Tea, Herbal Complementary, Pregnancy Monitoring ABSTRAK Setiap wanita hamil trimester 1 sering mengalami morning sickness. Jika tidak ditangani, dapat berkembang menjadi hyperemesis gravidarum yang menyebabkan dehidrasi berat, kerusakan organ, penurunan kesadaran, hingga kematian. Penelitian ini bertujuan membandingkan efektivitas wedang jahe dan wedang sereh lemon dalam mengurangi keluhan morning sickness pada ibu hamil trimester 1. Metode yang digunakan adalah Pre-Experiment dengan rancangan One Group Pretest Posttest Design dan pendekatan kuantitatif. Data dikumpulkan menggunakan kuesioner PUQE-24 pada 63 responden dengan purposive sampling. Wedang diberikan 2 kali sehari (250 ml) selama 1 minggu, lalu tingkat morning sickness dianalisis menggunakan uji Wilcoxon. Hasil menunjukkan nilai Sig. 2-Tailed 0,000 (p-value < 0,05), sehingga Ha diterima. Berdasarkan nilai mean, wedang sereh lemon lebih efektif dibandingkan wedang jahe. Keduanya dapat menjadi upaya nonfarmakologis dalam asuhan kebidanan komplementer untuk mengurangi morning sickness. Dukungan pemerintah diperlukan untuk memastikan bahan herbal terjangkau oleh semua kalangan. Kata Kunci: Morning Sickness, Wedang Jahe, Wedang Sereh Lemon, Komplementer Herbal, Pemantauan Kehamilan